In vitro digestion of short-dough biscuits enriched in proteins and/or fibres using a multi-compartmental and dynamic system (2): Protein and starch hydrolyses. (1st January 2016) - Villemejane, C.; Denis, S.; Marsset-Baglieri, A.; Alric, M.; Aymard, P.; Michon, C.
Highlights: In vitro digestion of biscuits carried out using a dynamic and multi-compartmental system. Comparison of the kinetics of digestion between enrichments in proteins, fibres and both of them. Following proteolysis upon digestion through the different gut compartments. Following amylolysis upon digestion through the different gut compartments. Abstract: The influence of protein and/or fibre enrichment on the nutritional properties of biscuits was studied in terms of proteolysis and amylolysis. Biscuits were digested using a multi-compartmental and dynamic system that simulates the main physiological digestive functions of the upper tract of healthy adult humans: the TIM-1. A control biscuit and three biscuits enriched in proteins and/or fibres were digested under the same conditions. Samples were collected in each compartment of the TIM-1 (stomach, duodenum, jejunum and ileum) at different times of digestion and analysed in terms of proteolysis and amylolysis. Results indicate that both formulation and processing impacted the digestive fate of the biscuits. Incorporating proteins or fibres in biscuits lowered or delayed proteolysis. Moreover a protein-plus-fibre additional or synergic effect was observed. Biscuits enriched in proteins and/or fibres displayed a higher amylolysis degree than the control biscuit, probably due to lower starch amounts and higher gelatinization degrees.